2022
DOI: 10.1631/jzus.b2101019
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive constituents of animal-derived traditional Chinese medicinal materials for breast cancer: opportunities and challenges

Abstract: Breast cancer is globally the most common invasive cancer in women and remains one of the leading causes of cancer-related deaths. Surgery, radiotherapy, chemotherapy, immunotherapy, and endocrine therapy are currently the main treatments for this cancer type. However, some breast cancer patients are prone to drug resistance related to chemotherapy or immunotherapy, resulting in limited treatment efficacy. Consequently, traditional Chinese medicinal materials (TCMMs) as natural products have become an attracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 157 publications
(165 reference statements)
0
3
0
Order By: Relevance
“…These pathways are involved in the anti-tumor, inflammatory response, antioxidant, hormone regulation, cell proliferation, and cell cycle functions, and other functional areas. In this research, a total of 66 targets were annotated into the cancer pathway, and the literature shows that deer antler is widely used in the treatment of cancer [ 48 , 49 ]. Through enrichment analyses, we found that the core targets were widely distributed in the PI3K/AKT signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways are involved in the anti-tumor, inflammatory response, antioxidant, hormone regulation, cell proliferation, and cell cycle functions, and other functional areas. In this research, a total of 66 targets were annotated into the cancer pathway, and the literature shows that deer antler is widely used in the treatment of cancer [ 48 , 49 ]. Through enrichment analyses, we found that the core targets were widely distributed in the PI3K/AKT signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…According to statistics, the current Chinese Pharmacopoeia (2020 edition) has documented 49 varieties of animal-derived TCMs and even 497 prescription preparations containing animal-derived TCMs [55]. Unfortunately, the complex macromolecular constitutes in animal-derived TCMs have not been thoroughly researched, compared to these bioactive small molecular components in plant-derived TCMs [56]. The previous studies were apt to explore the bioactivities of proteins or peptides in medicinal animal products, such as Centipede, Snake venom, Wasp venoms, Pilose antler [57][58][59], and Chinese giant salamander.…”
Section: Discussionmentioning
confidence: 99%
“…edu/AP, accessed on 31 December 2023), and most were identified from animals, especially insects. As one of the most ancient chelicerates that have evolved over an estimated 430 million years, scorpions belong to the phylum Arthropoda, class Arachnida, and order Scorpionida and have traditionally been used for medicinal purposes in some Asian and African countries [18][19][20]. Because the physical process of venom injection may damage the caudal ganglia, resulting in further pathogen infection, it is expected that scorpions would possess an antimicrobial response system comprising unique mechanisms, such as AMPs, to protect themselves from microbe invasion [21,22].…”
Section: Introductionmentioning
confidence: 99%